If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(a + 3) + 5 = 0 Reorder the terms: 9(3 + a) + 5 = 0 (3 * 9 + a * 9) + 5 = 0 (27 + 9a) + 5 = 0 Reorder the terms: 27 + 5 + 9a = 0 Combine like terms: 27 + 5 = 32 32 + 9a = 0 Solving 32 + 9a = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-32' to each side of the equation. 32 + -32 + 9a = 0 + -32 Combine like terms: 32 + -32 = 0 0 + 9a = 0 + -32 9a = 0 + -32 Combine like terms: 0 + -32 = -32 9a = -32 Divide each side by '9'. a = -3.555555556 Simplifying a = -3.555555556
| n=-11+33 | | 5b-6-10b-8= | | 5y=67 | | (9x+3)(7x+1)= | | -6(0.2x+0.3)-3.2=-0.2 | | h(t)=-16t^2+50t+1 | | 4q^8+9r^2= | | x^4-x^3-5x^2+3x+6=0 | | 11-2x=-4x+3 | | (6x+6)(3x^2+7x+8)= | | x^4-x^3-5x^2+3x=6 | | 2y^2+30xy-2y^2+4y-4x= | | 4x^3-15x^2+25x=0 | | 11=2g+6-5g | | 26=30-26a | | f(2)=2x-1 | | 2x+2.5=9.5 | | 15=-6(2q-1) | | 4(5c-1)-4=18c+4 | | 5x+2-8x=4(8-x)+x | | 6x^2-6x+73=0 | | 15x^2=3 | | 15x^2=3 | | (10)(10)=(x+2)(x+2)+x^2 | | (x+10)(x+10)=2x+19 | | 45m^2-96m=0 | | 4x+15=5-x | | 4x+15=-1+5 | | 5x-x-9x= | | 35=a(a+2) | | 2y-6=14y+90 | | 25-6x=15+5x |